Factors Affecting the Developing Village Index (IDM) in the North Lampung Regency Area - M. Irfan Hammadi Ahadis; Teguh Endaryanto; Ktut Murniati (International Journal Labs, 2025)
The Developing Village Index (IDM) is a crucial indicator to measure the progress of village development in North Lampung Regency. This study aims to analyze the status and performance of IDM in North Lampung Regency during the 2018-2023 period, identify factors influencing the IDM values, and formulate strategies to improve the IDM based on the analysis. The research employs a narrative descriptive method to describe IDM status and performance, panel data regression to examine the influence of independent variables—village funds, village fund allocation, population density, and poor population—on the IDM, and SWOT analysis to develop effective strategies for IDM improvement. Results show that IDM performance in several sub-districts experienced stagnation or decline, with no village achieving independent status by 2023. Regression analysis indicates that simultaneously village funds, village fund allocation, population density, and poor population significantly affect IDM, with fund allocation, population density, and poor population having partial significant effects. Recommended strategies include enhancing human resources through training, optimizing village management based on digital technology, developing economic and tourism potential, improving tourism sector supervision, and advancing village product development. This study recommends local government evaluate and monitor village fund utilization effectively to boost IDM performance and encourages village governments to identify and develop village potentials in synergy with regional authorities.